THE LATEST CHALLENGES FOR HIGHER EDUCATION INSTITUTIONS - Ginevicius, R.; Valiulis, A. V.; Zavadskas, E. K. (Proceedings of National Aviation University (archive), 2021)
The beginning of a new millennium coincided with the period of renovation and reforms of universities. Universities should be the leaders and help the society to adopt new charac eristic elements of learning and to become a learning society. Aviation is the leading field where the modern knowledge and advanced research are applied. It the article an experience of the Lithu mia is analysed, Lithuania being a small country boasts a rich tradition in aviation and strives to par, icipate in this area of study and research.